Relationship between retinal inner nuclear layer, age, and disease activity in progressive MS. Issue 5 (September 2019) - Cellerino, Maria; Cordano, Christian; Boffa, Giacomo; Bommarito, Giulia; Petracca, Maria; Sbragia, Elvira; Novi, Giovanni; Lapucci, Caterina; Capello, Elisabetta; Uccelli, Antonio; Inglese, Matilde
Abstract : Objective: To investigate whether inner nuclear layer (INL) thickness as assessed with optical coherence tomography differs between patients with progressive MS (P-MS) according to age and disease activity. Methods: In this retrospective longitudinal analysis, differences in terms of peripapillary retinal nerve fiber layer (pRNFL), ganglion cell layer + inner plexiform layer (GCIPL), INL and T1/T2 lesion volumes (T1LV/T2LV) were assessed between 84 patients with P-MS and 36 sex- and age-matched healthy controls (HCs) and between patients stratified according to age (cut-off: 51 years) and evidence of clinical/MRI activity in the previous 12 months Results: pRNFL and GCIPL thickness were significantly lower in patients with P-MS than in HCs ( p = 0.003 and p < 0.0001, respectively). INL was significantly thicker in patients aged < 51 years compared to the older ones and HCs (38.2 vs 36.5 and 36.7 μm; p = 0.038 and p = 0.04, respectively) and in those who presented MRI activity (new T2/gadolinium-enhancing lesions) in the previous 12 months compared to the ones who did not and HCs (39.5 vs 36.4 and 36.7 μm; p = 0.003 and p = 0.008, respectively). Recent MRI activity was significantly predicted by greater INL thickness (Nagelkerke R 2 0.36, p = 0.001). Conclusions: INL thickness was higher in younger patients with P-MS with recent MRI activity, a criterion used in previous studies to identify a specific subset of patients with P-MS who best responded to disease-modifying treatment. If this finding is confirmed, we suggest that INL thickness might be a useful tool in stratification of patients with P-MS for current and experimental treatment choice.